Global environmental change : understanding the human dimensions - Stern, Paul C., 1944-; Young, Oran R.; Druckman, Daniel, 1939- (National Academy Press, 1992)
1. Prologue -- 2. Global change and social science -- 3. Human causes of global change -- 4. Human consequences and responses -- 5. Problems of theory and method -- 6. Data needs -- 7. Human resources and organizational structures -- 8. A National research program on the human dimensions of global change.